SOCIO-ECONOMIC BURDEN OF COVID-19 PANDEMIC ON THE YOUTH IN NIGERIA - DAWODU, Oluwatosin Abigail; EZEH, Sabastine Sunday; EZEH, Ann Nnenna (Socialscientia: Journal of Social Sciences and Humanities, 2021)
The COVID-19 pandemic affects several aspects of the human population, and more detrimental to the vulnerable including youth living in abject poverty and with disabilities. In order to understand the impact of the pandemic on the youth, this paper reviews the socio-economic burden of COVID-19 with specific attention on education, poverty, unemployment, and youth’s involvement in crimes. The objective is to proffer solutions to socio-economic problems triggered by the pandemic concerning the youth. The paper’s analysis is anchored on the structural functionalism approach being a theoretical review. This review argues that the pandemic came with difficult challenges, such as lockdown that have stagnated the lives of the youth, increased unemployment among them, and have also driven many into crimes. The paper recommends that the Nigerian government must cushion the effect of the socio-economic burden placed on youth by the pandemic through innovative and inclusive policy solutions targeted to promote employment and a healthy workforce in ways that would reduce poverty and crime rate among the youth.